Potency of fermented jicama extract cultured with Lactobacillus plantarum B1765 for producing short chain fatty acid - Avissa Auryn Wijayanti; Prima Retno Wikandari (Jurnal Pijar Mipa, 2023)
Short-chain fatty acid (SCFA) is the end product of inulin metabolism, which has various health benefits, such as affecting lipid metabolism and as an antidiabetic agent. This research studied the effect of the fermentation time of jicama extract with Lactobacillus plantarumB1765 as a starter culture on producing SCFA. Fermentation was conducted for 2, 12, 24, and 36 hours at a temperature of 37°C with 5% (v/v) of the starter culture, then determined the growth of LAB, pH, Total Titratable Acid (TTA), fructose, and Short Chain Fatty Acid content. The total LAB count was measured using the Total Plate Count; fructose was measured using the Nelson-Somogyi method, while SCFA was measured using HPLC with eluents H3PO4 0.1% and acetonitrile 25%. The length of fermentation affected the increase in total Lactic Acid Bacteria (LAB), Total titratable acidity (TTA), fructose, SCFA, and the decrease in pH. The results showed that the optimal growth of Total LAB at 24 hours of fermentation correlated with fructose content, but increasing TTA and SCFA until 36 hours of fermentation and pH decreased to 3,92 at the end of fermentation and decreasing pH due to lactic acid and SCFA producing. SCFA was identified as consisting of acetic acid (1.31±0.006 mg/mL), propionic acid (1.58±0.0055mg/mL), and butyric acid (1.05±0.0038mg/mL), with the highest SCFA was propionic acid. Therefore, fermented jicama extract with Lactobacillus plantarum B1765 has the potential to produce SCFA, which could be used for various health benefits.